Efektifitas Terapi SEFT (Spiritual Emotional Freedom Technique) untuk Mengurangi Perilaku Merokok Remaja Madya - Yupiter Sulifan; Suroso Suroso; Abdul Muhid (Jurnal Psikologi Tabularasa, 2014)
The purpose of this study was to determine the effectiveness of therapy SEFT to reduce smoking behavior in middle adolescence. The subjects were students at SMAN 1 Taman Sidoarjo ever smoked at school, the number of smokers was 24 students. These students were smokers every day on average spend cigarettes no more than 14 cigarettes. The subjects were given a pretest (lots of cigarettes smoked every day), therapy was given SEFT the next round. Posttest performed 2 days after therapy SEFT. Based on the analysis of the Wilcoxon Signed Ranks Test , the value of Z = - 4.564 , the Sig = 0.000 ( p 0.01 ) , so it can be said there was a difference between pretest and posttes , and the mean pre-test ( 4,000 ) the mean post- test ( 2.208 ), which means more subjects smoked a cigarette before SEFT therapy compared to after SEFT . This means SEFT therapy proved effective in reducing smoking behavior on adolescent students.